The carotid body and associated tumors: updated review with clinical/surgical significance. (3rd September 2019) - Butt, Nasir; Baek, Woong Kee; Lachkar, Stefan; Iwanaga, Joe; Mian, Asma; Blaak, Christa; Shah, Sameer; Griessenauer, Christoph; Tubbs, R. Shane; Loukas, Marios
Abstract: Purpose: The carotid body functions as a chemoreceptor and receives richer blood supply, by weight, than any other organ in the body. We review the literature regarding the anatomy, histology, and function of the carotid body and the incidence, functionality, and clinical relevance of carotid body tumors and paragangliomas. These lesions are often nonfunctional but can be associated with catecholamine secretion. Most patients are asymptomatic or present initially with a cervical mass. As the tumors grow, they can impinge on nearby cranial nerves. Although there is some debate, the dominant clinical strategy is to surgically resect these tumors as early as possible. If they are resected early, the risk of postoperative neurovascular injury is minimized. Methods: Literature search was performed using the PubMed database with focus on articles including descriptions of the carotid body and associated tumors. Results: We reviewed recent literature that related to the anatomy of the carotid body while also including carotid pargangliomas and associated diagnosis with treatment interventions. Conclusion: As the carotid body serves as a vital modulator of cardiovascular and respiratory functions, illustrates the importance of identifying potential carotid paragangliomas due its ability to impede function of the carotid body. By understanding carotid paraganglioma's distinct etiologies while also understanding proper diagnosis of tumors allows for early detection and appropriate treatment options.